2010
DOI: 10.4321/s1886-36552010000300005
|View full text |Cite
|
Sign up to set email alerts
|

Pattern and quality of scientific communications on drug safety produced by a regional pharmacovigilance center in Nepal

Abstract: Analyzing the pattern and quality of scientific communications on pharmacovigilance can help the regional centers in Nepal and other developing countries to develop approaches for communicating effectively medicine safety issues. This kind of research is lacking in developing countries.Objectives:To analyze the pattern and quality of scientific communications on drug safety produced by the regional pharmacovigilance center at western Nepal.Methodology:Various conference abstracts and journal publications produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 15 publications
2
1
0
Order By: Relevance
“…In a study done by Routledge et al [14] this incidence was estimated at 80% of all ADRs occurring in an hospital, knowing the drug dose that is causing an ADR can help prevent it in the future by optimizing to a safe dose. Impicciatore & Mucci [8] and Palaian et al [11] showed that 15% & 22.2% researchers had failed to report suspect drug dosage, which is consistent to our study finding of 16%. Knowing about the doses leading to a particular ADR is of great importance because it can give a new range of dose leading to the ADR that might be useful in formulating new treatment guidelines e.g.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In a study done by Routledge et al [14] this incidence was estimated at 80% of all ADRs occurring in an hospital, knowing the drug dose that is causing an ADR can help prevent it in the future by optimizing to a safe dose. Impicciatore & Mucci [8] and Palaian et al [11] showed that 15% & 22.2% researchers had failed to report suspect drug dosage, which is consistent to our study finding of 16%. Knowing about the doses leading to a particular ADR is of great importance because it can give a new range of dose leading to the ADR that might be useful in formulating new treatment guidelines e.g.…”
Section: Discussionsupporting
confidence: 92%
“…In our study we found that, amongst the required parameters, majority of the researchers have described most of the patient & ADR related details adequately (>90% reporting) (Table 1 & 3) and this finding is well supported by the studies done by Impicciatore & Mucci 8 and Palaian et al [11] . However, when it came to reporting drug related details in the ADR case report, we felt that the researchers largely fell short.…”
Section: Discussionsupporting
confidence: 80%
“…13 carried out a study that analyzed the pattern of literature in patient safety that suggests research directions for the future. The latter study showed the frequency of published articles and types of publications regarding PV and ADRs, 14 whereas our present study focuses on the impact of those published papers in different journals.…”
Section: Introductionmentioning
confidence: 90%